2005
DOI: 10.1038/ncpcardio0274
|View full text |Cite
|
Sign up to set email alerts
|

The role of shear stress in the generation of rupture-prone vulnerable plaques

Abstract: Blood-flow-induced shear stress acting on the arterial wall is of paramount importance in vascular biology. Endothelial cells sense shear stress and largely control its value in a feedback-control loop by adapting the arterial dimensions to blood flow. Nevertheless, to allow for variations in arterial geometry, such as bifurcations, shear stress control is modified at certain eccentrically located sites to let it remain at near-zero levels. In the presence of risk factors for atherosclerosis, low shear stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
192
3
7

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 303 publications
(209 citation statements)
references
References 54 publications
7
192
3
7
Order By: Relevance
“…21,22 The role of systemic factors such as inflammation 6 and lowdensity lipoprotein cholesterol 7 in the development of plaque vulnerability has been well documented. Recent interest has focused on the role of local factors, such as shear stress, in the development of high-risk coronary sites 5,23 and the genesis and progression of coronary atherosclerotic lesions. Atherosclerotic lesions predominantly occur in curved arteries and near side branches where wall shear stress is low.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21,22 The role of systemic factors such as inflammation 6 and lowdensity lipoprotein cholesterol 7 in the development of plaque vulnerability has been well documented. Recent interest has focused on the role of local factors, such as shear stress, in the development of high-risk coronary sites 5,23 and the genesis and progression of coronary atherosclerotic lesions. Atherosclerotic lesions predominantly occur in curved arteries and near side branches where wall shear stress is low.…”
Section: Discussionmentioning
confidence: 99%
“…Pathophysiologically, low shear stress is thought to induce loss of the physiologic floworiented alignment of endothelial cells, thereby increasing the expression of adhesion molecules and weakening cell junctions, ultimately leading to increased permeability of vascular tissue to lipids and macrophages. 5,[28][29][30] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that high values of TGWSS over 35.5 Pa/s are related to the expression of atherogenesisrelated genes in endothelial cells [25,26]. This may indicate the vulnerability of the narrowing regions that may potentially suffer from atherosclerosis.…”
Section: Loading Distributionsmentioning
confidence: 99%
“…WSS is reported to be related to endothelial cell function and is an important factor in the progression of atherosclerosis [21,22]. High WSS over 30 Pa may induce desquamation of endothelial cells, platelet aggregation, intimal injury or rupture of vulnerable plaques [23,24]. The WSS distributions in all of the cases are below 30Pa, except for the stenosis at the carotid bulb and the proximal ICA of PIII.…”
Section: Volume Flow Ratementioning
confidence: 99%